Vozes sociais na "não-pessoa": circulação dialógica no processo de letramento - Trombetta, Vanda Mari (2017)
That which comes in the third person, that about which one says / writes, when it is considered a product of authors / addressees interactions, brings, by referring to an already-said, brings a third element (a third voice) in the composition of discourse objects. This last, due to also constitute itself from an already-said, a social voice, expressa reply from the addresser, in accordance with the many several positions the different social experiences that the addresser, as the author, takes in interactions. To think discourse objects as social voices is, thus, to accept it as a product of addressers replies to addressees (BAKHTIN, [1979] 2010a 2006), which allows to think not only about the present interaction, but also as its constitutive element on possible utterances linked by addressers to social practices authors bring to bear on their texts. For doing this, by accepting the participation of a third in language production, we aim to describe it, as regards college entrance exam texts, in terms of voices that participate in college entrance exam texts and define them according to school practices authors have had or have (direct or indirect) access. The theoretical foundation sof dialogical analysis (BAKHTIN [1961-1962, 1975, 1979] 2010 a, b, c) and the CIRCLE), modern rhetoric (PERELMAN; OLBRECHTS-TYTECA, 2005), literacy theories (STREET, 2012b, 2014), and the indiciary paradigm (GINZBURG, 1989), are taken as the works theoretical-methodological basis. Thus, phenomena are examined that mobilize the emergence of marks materialized in texts, phenomena at the same time linked to the specificities of the immediate enunciative situation, on the one side, and to what appear as elements stabilized in and by interactions throughout history, on the other. The corpus is composed by 264 FUVEST 2006 college entrance exam texts having work as their subject. Results obtained show that the construction of the discourse object work is a dialogue among three rigorously present interlocutors in these written productions: the addresser/author, addressees and some identifiable voices of the already-said, whose marks are summoned in discourse objects, constituting them and imposing themselves on them.